ﺗﺪرﯾﺲ ﻣﮭﺎرات اﻟﻠﻐﺔ اﻟﻌﺮﺑﯿﺔ ﺑﺎﺳﺘﺮاﺗﯿﺠﯿﺎت اﻟﻌﺎدات اﻟﻌﻘﻠﯿﺔ ﺑﯿﻦ اﻟﺘﻨﻈﯿﺮ واﻟﺘﻄﺒﯿﻖ (Journal of the College of Education for Women, 2019)
Arabic first is a basic function that makes the communicative process easy, and the learner should control the skills of listening, speaking and reading and wring. Listening is a complex skill that includes prediction and interpretation and the discovery of the relationships and meanings,speaking a productive process which translates the mental images and includes the patterns of thinking and analysis and justifications and the problem solving. Writing,one the other hand,is an intellectual,lingual,productive process that is based on the elements of thinking and formulation. Modern strategies could be employed to teach the skills of communication in Arabic, such as mental habits strategies which include: persistence, flexible thinking, questioning, problem posing, creativity and imaging, mutual thinking, thinking,thinking about thinking.